ANALISIS ONLINE CUSTOMER REVIEW DAN ONLINE CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN SHOPEE - Angraeni, Ni Luh Ayu; Made, Sudarma I; Rieka, Widaswara Yulita (Waisya : Jurnal Ekonomi Hindu, 2024)
The study aims to analyze online customer reviews and online customer ratings on the decision to purchase Shopee. In this study, there are two independent variables consisting of the variable Online customer reviews (X1) and variable Customer ratings (X2) and dependent variables that are the variables of the Buying Decision. (Y). This type of research uses quantitative research that is analyzed using statistics. The population in this study is the total active students of the State Hindu Religious Institute Gde Pudja Mataram which amounted to 1200 students. The sampling technique in this study uses the Purposive Sampling technology which uses certain criteria in samplings. As for the analytical tool used in this study, the IMB SPSS Statistic 25. As to the results obtained in the research conducted from the hypothesis testing, it can be concluded that 1) Online customer review has a positive and significant influence in part on the decision to purchase Shopee among the students of the State Hindu Institute of Gde Pudja Mataram. 2) Online customer rating has a significant and positive influence on the purchase decision of the Institute of Hindu Religion of Gde Pudja Mataram in part.